Католицькі, унійні та протестантські навчальні заклади на Волині в ХVІ – XVII ст. - Ткачук, Анатолій Петрович; Tkachuk, Anatolii P. (Волинська духовна семінарія, 2015)
Досліджено навчальні заклади на Волині в ХVІ – XVII ст. Проаналізовано створення та діяльність католицьких, унійних та протестантських навчальних закладів, їх навчально-методичне та кадрове забезпечення. Особливості навчального процесу.

Educational establishments in Volhynia in the seventeenth and seventeenth centuries were investigated. The creation and activity of Catholic, Uniate and Protestant educational institutions, their teaching and methodical and personnel support are analyzed. Features of the educational process.
Catholic, Uniate and Protestant Educational Institutions in Volhynia in the seventeenth and seventeenth centuries
Keywords: навчальні заклади; колегіум; сім вільних наук; єзуїти; уніати; протестанти; schools; collegium; seven free sciences; jesuits; uniates; рrotestants